Combined first-principles calculations and experimental study on the photocatalytic mechanism of natural dolomite. Issue 39 (12th July 2021) - Hou, Xiaomin; Cheng, Qi; Wang, Jianrong; Wu, Qingfeng; Zhang, Weibin
Abstract : Natural dolomite exhibits notable photocatalytic activity due to the isomorphous substitution of Fe 2+ for Mg 2+ in the lattice, implying that it can be used as a low-cost photocatalyst. Abstract : Mineral-based photocatalysts have received great attention due to their low cost. In this study, the photocatalytic activity of natural dolomite and its mechanism were investigated based on designed experiments and first-principles calculations. The kinetic study showed that natural dolomite showed notable photocatalytic activity for the degradation of target compounds including methylene blue, diphenhydramine, and tetracycline. The EPR analysis demonstrated that O2 − ˙, ˙OH, and 1 O2 were produced in the dolomite system under simulated sunlight irradiation. The first-principles calculations indicated that the isomorphous substitution of Fe 2+ for Mg 2+ in the dolomite lattice led to the impurity levels appearing in the forbidden band, which caused a significant decrease of the band gap from 5.02 to 1.63 eV. As a result, natural dolomite could act as a semiconductor photocatalyst in photochemical reactions due to the substitution of Mg 2+ by Fe 2+ . Under simulated sunlight irradiation, photogenerated electron–hole pairs in the natural dolomite were separated and transferred to the surface, and then formed reactive radicals through further reactions, thereby enhancing the degradation of target compounds. This research may contribute to the understanding of the photocatalytic activity of natural minerals.